ANALYSIS OF STUDENTS' CRITICAL THINKING SKILLS IN NATURAL AND SOCIAL SCIENCES CLASS IV SD MUHAMMADIYAH 1 NGIMBANG LAMONGAN - Kharisma, Ahmad Ipmawan; Huda, Mochammad Miftachul; Mudayan, Arfian; Khasanah, Miftakhul (Journal of Elementary Education, 2025)
This study aims to analyze the critical thinking skills of fourth grade students in the subject of Natural and Social Sciences (NSP) at SD Muhammadiyah 1 Ngimbang. The background of this study is the low critical thinking skills of students which is influenced by the use of media and learning methods that are still conventional and less interactive. This study used a descriptive qualitative approach with data collection techniques in the form of observation, interviews, and documentation studies. The results showed that the dominance of using textbooks as the main media causes learning to take place abstractly and monotonously, so that students become passive and have difficulty in understanding the material. Although the school has technology facilities, its utilization in learning is still minimal. The lack of contextual and interactive learning media causes low student concentration and has an impact on weak critical thinking skills and the application of knowledge in everyday life. This study recommends the use of more innovative learning media and teacher training in the utilization of technology to support critical thinking skills in accordance with the principles of Merdeka Curriculum.